Gold Seekers of '49 - Sabin, Edwin L. (Edwin Legrand), 1870-1952; Stephens, Charles H., 1851-1931 (Salt Lake City, UT : Project Gutenberg, 2007)
"Gold Seekers of '49" by Edwin L. Sabin is a historical adventure novel written in the early 20th century. The book follows Charley Adams and his father as they embark on an arduous journey from St. Louis to the gold fields of California during the 1849 Gold Rush. The narrative explores their experiences as they navigate challenges, encounter colorful characters, and pursue fortune in a land rapidly attracting fortune-seekers from around the world. At the start of the story, Charley trudges through a snowstorm while carrying mail home, filled with excitement over news of the California Gold Rush. Charley$1 (Bs father, recovering from injuries sustained during the Mexican War, yearns for a fresh start as California beckons with promises of wealth. Their fate changes when Charley discovers an unconscious stranger in the street, who turns out to be a gold miner returning from California. After rescuing the man, they learn of his heavy sacks filled with gold dust and a potential gold mine, setting in motion a series of events that will lead them westward. Thus, the book kickstarts an adventurous tale that captures the imagination and hope of those seeking their fortunes in the Wild West. (This is an automatically generated summary.)s
Release date is 2007-10-25
Produced by Al Haines
Keywords: Gold mines and mining -- Fiction; California -- Fiction